2021
DOI: 10.1155/2021/1425227
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Effect of Soft and Hard Coal Pore Structure on Gas Adsorption Characteristics

Abstract: In order to grasp the effect of soft and hard coal pore structure on gas adsorption characteristics, based on fractal geometry theory, low-temperature nitrogen adsorption and constant temperature adsorption test methods are used to test the pore structure characteristics of soft coal and its influence on gas adsorption characteristics. We used box dimension algorithm to measure the fractal dimension and distribution of coal sample microstructure. The research results show that the initial nitrogen adsorption c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…The utilization of adsorption is wide-ranging and encompasses diverse purification methodologies and the retrieval of vital constituents. Different studies (Salman et al, 2014;Hong et al, 2017;Çermikli et al, 2020;Zhao et al, 2021;Chen and Lo, 2022;Mohamed et al, 2023) show that molecular sieves and activated carbon have been used a lot to treat solutions. Batch, fixed bed, fluidized bed, moving bed, and pulsed bed are different process topologies commonly utilized in adsorption systems.…”
Section: Introductionmentioning
confidence: 99%
“…The utilization of adsorption is wide-ranging and encompasses diverse purification methodologies and the retrieval of vital constituents. Different studies (Salman et al, 2014;Hong et al, 2017;Çermikli et al, 2020;Zhao et al, 2021;Chen and Lo, 2022;Mohamed et al, 2023) show that molecular sieves and activated carbon have been used a lot to treat solutions. Batch, fixed bed, fluidized bed, moving bed, and pulsed bed are different process topologies commonly utilized in adsorption systems.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of soft and hard coal pore structure on gas adsorption was studied. The results showed that the PV and SSA of soft coal were comparatively higher than that of hard coal (Zhao et al 2021b). Though coal is used as the main energy source, pulverized coal is also the form of coal that can be used significantly for production (Shi et al 2021a, b).…”
Section: Introductionmentioning
confidence: 99%